ANALISIS MEKANISME PENGADAAN BUKU PAKET DI MADRASAH ALIYAH MA'HAD AL-ZAYTUN INDRAMAYU DALAM PERSPEKTIF PRINSIP AL-MASLAHAH IMAM SYATIBI - Siti Julaekha; Rizal Maulana; Imam Prawoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
In the procurement of package books at Madrasah Aliyah Ma'had Al-Zaytun Indramayu, sharia economic principles can be applied to ensure that transactions are conducted fairly, transparently, and in accordance with sharia provisions. As policy makers, it is necessary to support the application of these principles through regulations that facilitate the procurement of sharia-compliant goods and services, including in the education sector. The purpose of this research is to analyze the mechanism of package book procurement at Madrasah Aliyah Ma'had Al-Zaytun Indramayu, and to evaluate the suitability of package book procurement at Madrasah Aliyah Ma'had Al-Zaytun Indramayu with the perspective of Imam Syatibi's al-maslahah principle. This research method uses field research with a qualitative approach. The data collection procedures carried out were through observation, interviews, and documentation. Data analysis was carried out descriptively and interpretatively, using thematic, content, narrative, phenomenological, grounded theory, and discourse analysis techniques. The data were analyzed to explore an in-depth understanding of the social phenomenon or behavior under study. The results of the study concluded that: first, the mechanism of package book procurement at Madrasah Aliyah Ma'had Al-Zaytun involves discussions between related parties to select books, ordering after approval, book delivery, distribution to students, and payment through the E-MAZ application with the option of payment in full or 4-5 months installments. Second, the application of Imam Syatibi's al-maslahah principle in the procurement of package books has a positive impact on the quality of education and the welfare of students, guardians, and institutions. The curriculum-compliant policy and payment flexibility reflect efforts to achieve benefits without harming. Although there are negative impacts such as emotional burdens, this policy supports smooth learning. Keywords: package book procurement, madrasah aliyah, al-maslahah principle